Methane dynamics in vegetated habitats in inland waters: quantification, regulation, and global significance - Bodmer, Pascal; Vroom, Renske J. E.; Stepina, Tatiana; del Giorgio, Paul A.; Kosten, Sarian (Frontiers in Water, 2024)
Freshwater ecosystems, including lakes, wetlands, and running waters, are estimated to contribute over half the natural emissions of methane (CH4) globally, yet large uncertainties remain in the inland water CH4 budget. These are related to the highly heterogeneous nature and the complex regulation of the CH4 emission pathways, which involve diffusion, ebullition, and plant-associated transport. The latter, in particular, represents a major source of uncertainty in our understanding of inland water CH4 dynamics. Many freshwater ecosystems harbor habitats colonized by submerged and emergent plants, which transport highly variable amounts of CH4 to the atmosphere but whose This is a provisional file, not the final typeset article presence may also profoundly influence local CH4 dynamics. Yet, CH4 dynamics of vegetated habitats and their potential contribution to emission budgets of inland waters remain understudied and poorly quantified. Here we present a synthesis of literature pertaining CH4 dynamics in vegetated habitats, and we (i) provide an overview of the different ways the presence of aquatic vegetation can influence CH4 dynamics (i.e., production, oxidation, and transport) in freshwater ecosystems, (ii) summarize the methods applied to study CH4 fluxes from vegetated habitats, and (iii) summarize the existing data on CH4 fluxes associated to different types of aquatic vegetation and vegetated habitats in inland waters. Finally, we discuss the implications of CH4 fluxes associated with aquatic vegetated habitats for current estimates of aquatic CH4 emissions at the global scale. The fluxes associated to different plant types and from vegetated areas varied widely, ranging from -8.6 to over 2835.8 mg CH4 m -2 d -1 , but were on average high relative to fluxes in non-vegetated habitats. We conclude that, based on average vegetation coverage and average flux intensities of plant-associated fluxes, the exclusion of these habitats in lake CH4 balances may lead to a majorn underestimation of global lake CH4 emissions. This synthesis highlights the need to incorporate vegetated habitats into CH4 emission budgets from natural freshwater ecosystems and further identifies understudied research aspects and relevant future research directions.